The Use of YouTube Videos to Increase Student Motivation in Islamic Date Subjects - Chofivah, Astrid; Madjid, Abd. (Newinera Publisher, 2024)
This study aims to find out how the learning process uses YouTube videos, how students learn motivation by using YouTube videos, and whether there is an influence of YouTube videos on student learning motivation in Islamic Date subjects. The research uses quantitative methods with a quasi-experimental approach. Research place at SMK Muhammadiyah 1 Bantul with data collection with questionnaires, observations, and documentation. The data analysis technique used in this study used an independent t-test and a paired t-test. The learning process using YouTube videos is more effective because students are more interested in listening to the material displayed through YouTube videos. The results of the data analysis of this study showed that the use of YouTube videos in learning affected student learning motivation because the experimental class obtained an average of 54.08, while the control class obtained an average of 38.12. This shows that the average observation results of experimental classes using YouTube videos are higher than conventional classes that do not use YouTube videos. From the results of the one-sample t-test test data, the results showed a significance value (2-tailed) of 0.000 < 0.05, which means that H0 is rejected and Ha is accepted. So it can be concluded that the use of YouTube videos in learning influences student learning motivation. By the results of the experimental and control class N-Gain, the average percentage of N-Gain class X TKRO 1 as an experiment was 57.9097% with the effective category, and class X TPM 1 obtained an average N-Gain percentage of 38.0658% with the ineffective category.